1987
DOI: 10.1111/j.1524-4725.1987.tb00507.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Laser Blepharoplasty: A Comparison to Cold Steel and Electrocautery

Abstract: Thirteen patients underwent blepharoplasty in a paired comparison study. A carbon dioxide laser was employed for one side while standard cold steel surgery and electrocautery was used on the contralateral side. In addition to reduced intraoperative time and bleeding, we found less postoperative ecchymosis and edema on the laser-treated side. Long-term follow-up showed no difference between the two sides when cosmetic end result and scars were compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…The longer operating times and intraoperative hemorrhage lead to bruising, swelling, and tissue distortion. 16 Although some authors report that the CO 2 laser offers little advantage over the scalpel, 17 a recent survey comparison of scalpel versus CO 2 laser blepharoplasty indicated laser benefits, including quicker recovery time to usual activities (6.3 vs. 9.1 days) and shorter operating times (four eyelid blepharoplasty times of 58 vs. 94 minutes). 18 In another study, Biesman et al performed upper blepharoplasty on 35 patients using laser on one side and traditional instruments on the other.…”
Section: Co 2 Laser To Other Incisional Methodsmentioning
confidence: 99%
“…The longer operating times and intraoperative hemorrhage lead to bruising, swelling, and tissue distortion. 16 Although some authors report that the CO 2 laser offers little advantage over the scalpel, 17 a recent survey comparison of scalpel versus CO 2 laser blepharoplasty indicated laser benefits, including quicker recovery time to usual activities (6.3 vs. 9.1 days) and shorter operating times (four eyelid blepharoplasty times of 58 vs. 94 minutes). 18 In another study, Biesman et al performed upper blepharoplasty on 35 patients using laser on one side and traditional instruments on the other.…”
Section: Co 2 Laser To Other Incisional Methodsmentioning
confidence: 99%
“…Laurence et al 17 conducted an RCT to compare the efficacy of CO 2 laser blepharoplasty with that of cold steel and electrocautery. Thirteen cases were included, and the results showed less bleeding on the laser side and a good correlation between decreased operative time and decreased bleeding when compared with the cold steel surgery side.…”
Section: Part I Systematic Reviewmentioning
confidence: 99%
“…We observed that in later operations, surgeons could incise with electrocautery quicker than during prior operations and sometimes quicker than when using the scalpel. In a systematic review, the authors found five previous studies [17][18][19][20][21] on Colorado needle electrocautery for upper eyelid skin incision; however, among these articles, they did not have an RCT study to compare Colorado needle electrocautery and a scalpel in upper blepharoplasty incision with respect to bleeding during skin incision and scarring using standard evaluation. Moreover, there were no previous studies on Asian people with poor scar outcomes compared with White people.…”
Section: Prs Global Open • 2023mentioning
confidence: 99%
“…1,2 Studies have evaluated the various modalities of removing excess eyelid skin based on time to perform the surgical procedure, amount of intraoperative bleeding, scar cosmesis, postoperative healing outcomes, and cost. [3][4][5][6][7][8][9] Historically, electrocautery has been avoided in aesthetic blepharoplasty because of concerns for surrounding tissue injury leading to increased scarring, damage to surrounding skin appendages, immediate postoperative ecchymosis, tissue edema, and possible nidus for infection. 3,8,10 The newer Colorado needle tip (Stryker, Inc., Kalamazoo, MI) allows for a more precise delivery of energy as compared to the broader electrodes used in traditional electrocautery.…”
mentioning
confidence: 99%